2017
DOI: 10.1167/iovs.16-20504
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Functional Lentoid Bodies From Human Induced Pluripotent Stem Cells Derived From Urinary Cells

Abstract: Citation: Fu Q, Qin Z, Jin X, et al. Generation of functional lentoid bodies from human induced pluripotent stem cells derived from urinary cells. Invest Ophthalmol Vis Sci. 2017;58:517-527. DOI:10.1167/ iovs.16-20504 PURPOSE. The pathological mechanisms underlying cataract formation remain largely unknown on account of the lack of appropriate in vitro cellular models. The aim of this study is to develop a stable in vitro system for human lens regeneration using pluripotent stem cells. METHODS.Isolated hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 29 publications
2
65
0
Order By: Relevance
“…Western blot analysis revealed the expression of LC3BII in mature LBs in our previous study. 24 Thus, the expression patterns of LC3B and P62 at different time points during LB differentiation as well as the location of LC3B were examined. Our results showed that more LC3B and less P62 were expressed in differentiating LBs after D14 when massive lens epithelial cells differentiated to fiber cells with organelle degradation ( Figures 2 A–2D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Western blot analysis revealed the expression of LC3BII in mature LBs in our previous study. 24 Thus, the expression patterns of LC3B and P62 at different time points during LB differentiation as well as the location of LC3B were examined. Our results showed that more LC3B and less P62 were expressed in differentiating LBs after D14 when massive lens epithelial cells differentiated to fiber cells with organelle degradation ( Figures 2 A–2D).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study established an efficient system—a “fried egg” method for human lens regeneration in vitro from both embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs). 24 The lens generated in the dish (also known as the lentoid body [LB]), which showed a lens-like transparent structure, not only expressed lens-specific markers but also exhibited basic optical characteristics. More importantly, in addition to lens-specific markers, including α, β, γ-crystallins, and MIP, the expression of placodal markers, such as SIX1 and PAX6, and early lens-specific markers, such as SOX1 and PROX1, were also observed at certain time points of LB differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Celojevic et al 29 were also not able to detect E-cadherin expression by immunohistochemistry and by western blot in human lens epithelial cells derived from cataract surgery in patients. On the contrary, Fu et al 10 were able to detect E-cadherin in lentoid bodies made from humaninduced pluripotent stem cells derived from urinary cells.…”
Section: Spheroids Made From Human Lens Epithelial Cells Are Rapidly mentioning
confidence: 90%
“…5,6 Several lens in vitro models have been explored in the past including however not limited to primary and immortalized cell lines, 7,8 whole lens culture, 9 and lentoid bodies. 10 Although the benefit of cell line-derived models is the reproducibility and availability of cells, 11 whole lens cultures isolated from different species like rats 9 or mice 12 offer a great structural similarity to in vivo models. However, translation to human from animal lens explants seems to be challenging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation